Analysis of Cost of Production - Macvane, S. M. (Quarterly Journal of Economics, 1887)
Journal Article Analysis of Cost of Production Get access S. M. Macvane S. M. Macvane Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 4, July 1887, Pages 481–487, https://doi.org/10.2307/1879343 Published: 01 July 1887